Implementasi IoT untuk Monitoring Kecepatan Angin di Pesisir Pantai Kenjeran Surabaya - Fery Soewarianto; Danang Haryo Sulaksono; Gusti Eka Yuliastuti; Citra Nurina Prabiantissa (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2022)
Wind is air that moves due to differences in air pressure. Wind moves from areas of high air pressure to areas of low air pressure. The wind also affects the height of the sea waves where the faster the wind speed that blows, the higher the sea waves. This will greatly affect fishermen to go to sea. Based on current conditions with limited equipment available, fishermen have difficulty measuring the wind speed that is occurring when the fishermen are about to go to sea. The solution proposed by the author is to implement the Internet of Things (IoT). The author will develop a sensor tool to measure and detect the level of wind speed combined with a windmill using Arduino Uno and NodeMCU ESP8266. The measurement results are displayed through a mobile application that can be accessed directly by fishermen on the Kenjeran coast of Surabaya